Respuesta :

Answers:

a = 3

b = 3

c = -6

=====================================

Explanation:

The roots are x = 1 and x = -2. This leads to the factors x-1 and x+2 respectively.

This is because something like x = 1 becomes x-1 = 0 after subtracting 1 from both sides. For x = -2, we add 2 to both sides getting x+2 = 0.

The factorization is y = a(x-1)(x+2)

Plug in (x,y) = (2,12) and solve for 'a'

y = a(x-1)(x+2)

12 = a(2-1)(2+2)

12 = a(1)(4)

12 = 4a

12/4 = a

3 = a

a = 3

So we have y = a(x-1)(x+2) update to y = 3(x-1)(x+2)

--------------------------------------

The last thing we need to do is expand everything out (use the FOIL rule then distributive rule) to get the equation into standard form

y = 3(x-1)(x+2)

y = 3(x^2+2x-1x-2)

y = 3(x^2+x-2)

y = 3x^2+3x-6

Comparing this to y = ax^2+bx+c shows that:

a = 3

b = 3

c = -6

The graph is below.

Ver imagen jimthompson5910